2011
DOI: 10.3989/revmetalmadrid.1003
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation behaviour at 1123 K of AISI 304-Ni/Al-Al<sub>2</sub>O<sub>3</sub>/TiO<sub>2</sub> multilayer system deposited by flame spray

Abstract: The oxidation behaviour of alumina/titania (97/3, 87/13 and 60/40) ceramic coatings using a Ni-Al coupling layer was studied in a thermobalance. Both layers were deposited on an AISI 304 stainless steel base metal by the flame spray technique. The coated steel was heated from room temperature to 1,123 K at 40 K min -1 , oxidized in air for 50 h, and then cooled to room temperature at 40 K min -1 . The mass gain was mainly attributed to the oxidation of Ni-Al coupling layer. Kinetic laws, DW·S -1 (mg.mm -2 ) vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In previous works (Ref 16,17), the effectiveness of OF thermal spray technique to improve the tribological behavior and oxidation protection of stainless steels at 850°C was proven with a coating system composed of a Ni-Al alloy bond coat and a ceramic topcoat. In a more recent work (Ref 18), it was shown that NiCrAlY thermally sprayed by the OF thermal spray technique provides good oxidation resistance to AISI 304 and AISI 316 stainless steels for temperatures as high as 1000°C for 50 h.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works (Ref 16,17), the effectiveness of OF thermal spray technique to improve the tribological behavior and oxidation protection of stainless steels at 850°C was proven with a coating system composed of a Ni-Al alloy bond coat and a ceramic topcoat. In a more recent work (Ref 18), it was shown that NiCrAlY thermally sprayed by the OF thermal spray technique provides good oxidation resistance to AISI 304 and AISI 316 stainless steels for temperatures as high as 1000°C for 50 h.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7 shows the XRD difraction peaks for aluminatitania coated SS. An intense peak was recognized around 22 °due to the alumina-titania coating [33]. Te peaks of 33 °and 50 °could also relate to the alumina-titania coating.…”
Section: Sem X-ray Difraction and Hardness Analysis Of Thementioning
confidence: 93%